2006
DOI: 10.1186/1471-2350-7-17
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a gene influencing heart rate on chromosome 5p13-14 in a meta-analysis of genome-wide scans from the NHLBI Family Blood Pressure Program

Abstract: Background: Elevated resting heart rate has been shown in multiple studies to be a strong predictor of cardiovascular disease. Previous family studies have shown a significant heritable component to heart rate with several groups conducting genomic linkage scans to identify quantitative trait loci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Heart rate, often more accurately measured as the length in milliseconds of the RR interval (heart rate = 60,000/RR), is a well known risk factor for morbidity in cardiovascular disease1,2 and all-cause mortality 3. Heritability, linkage, and association studies have suggested that RR interval is modified by common genetic variations4,5 but no RR modifier variants have yet been consistently confirmed.…”
mentioning
confidence: 99%
“…Heart rate, often more accurately measured as the length in milliseconds of the RR interval (heart rate = 60,000/RR), is a well known risk factor for morbidity in cardiovascular disease1,2 and all-cause mortality 3. Heritability, linkage, and association studies have suggested that RR interval is modified by common genetic variations4,5 but no RR modifier variants have yet been consistently confirmed.…”
mentioning
confidence: 99%
“…Thus, MYOZ2 may indirectly influence calcium signaling and pacemaker function in the heart. In a larger study of 3,282 Caucasian and African-American populations (Family Blood Pressure Program) two loci were found [24]. A significant locus on chromosome 10 (142.78cM; LOD=4.6) was linked to HR in the Caucasian group of HyperGEN.…”
Section: Genetics Of Hr Trait In Humansmentioning
confidence: 97%
“…A significant locus on chromosome 10 (142.78cM; LOD=4.6) was linked to HR in the Caucasian group of HyperGEN. However, a common region on chromosome 5p13-14 (LOD=1.9) influenced HR in both races [24]. Genome-wide linkage for HR showed a peak on chromosome 18 (77cM; LOD = 2.03) in 73 Mongolian families [25].…”
Section: Genetics Of Hr Trait In Humansmentioning
confidence: 99%
“…Singh et al, (2002) identified significant genetic regions contributing to heart rate variability on chromosome 15 at 62 cM and chromosome 2 at 153 cM. In the recent meta-analysis of genome-wide scans for study networks that enrolled Caucasians and AfricanAmericans, Laramie et al (2006) concluded in the replication between various ethnic groups as well as the study networks with low heterogeneity on chromosome 5p13-14. Wilk et al (2002) also identified that 195.06 cM region of chromosome 4 is seemingly related to the variability in resting heart rate.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for elevated heart rate and its association with such diseases and death is still not well understood. A number of twin and family studies have reported that genetic factors influence the regulation of heart rate (Singh et al, 1999;Woodman et al, 2002;Wilk et al, 2002;Martin et al, 2004;Neumann et al, 2005;Laramie et al, 2006;Larson et al, 2007;Newton-Cheh et al, 2007;O'Donnell et al, 2007). Voss et al (1996) reported that there is a genetic component in heart rate generation and heart rate variability in monozygotic and dizygotic twin pairs.…”
Section: Introductionmentioning
confidence: 99%